PHARMACOEPIDEMIOLOGY : A REVIEW - Upadhyay, Srishti; Shrivastava, Saumya; Kumar, Deepak; Kabra, Atul; Baghel, Uttam Singh (Asian Journal of Pharmaceutical Research and Development, 2019)
Pharmacoepidemiology is the study of the use of drugs in a large number of people.It is a growing discipline that applies epidemiological techniques to study drugs used in a large population. Just as the term implies, pharmacoepidemiology combines clinical pharmacology with epidemiology. Pharmacology is the study of the effects of medications on humans; it pertains to using pharmacokinetic and pharmacodynamic parameters of patients to predict the effect of drugs. Epidemiology, on the other hand, is the study of the factors that determine the occurrence and distribution of diseases in a population. In its broad concept, it encompasses drug utilization studies, and identification and quantification of adverse drug reactions (ADRs); its aim is to improve the quality and use of medicines. Drug utilization studies are known to involve the marketing, distribution, prescription, and use of drugs in a society with special emphasis on the medical, social, and economic consequences. The discipline, when not considered sufficiently, has a potential that could cause a high-level of increase in health expenses by creating conflict in the health systems of countries. In this study, it is aimed to define pharmacoepidemiology, to analyze its relation with other disciplines and to inform about pharmacoepidemiology usage areas.